2015
DOI: 10.1111/jfd.12340
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cyprinid herpesvirus 2 in peripheral blood cells of silver crucian carp, Carassius auratus gibelio (Bloch), suggests its potential in viral diagnosis

Abstract: Epidemics caused by cyprinid herpesvirus 2 (CyHV-2) in domestic cyprinid species have been reported in both European and Asian countries. Although the mechanisms remain unknown, acute CyHV-2 infections generally result in high mortality, and the surviving carps become chronic carriers displaying no external clinical signs. In this study, in situ hybridization analysis showed that CyHV-2 tended to infect peripheral blood cells during either acute or chronic infections in silver crucian carp, Carassius auratus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
(84 reference statements)
1
21
0
Order By: Relevance
“…Products from AGE and LFD were compared. A standard PCR protocol for the detection of infectious CyHV‐2 (Wang, Xu & Lu ) was also performed using specific primer pair CyHV‐2F (CCTCCGTATCTTTGGGGACT) and CyHV‐2R (ATGATGCCCTCAAAGGTGTC); Table . PCR amplification conditions were as follows: initial denaturation at 98°C for 1 min, followed by 35 cycles of 10 s at 98°C, 10 s at 55°C and 60 s at 72°C, and a final extension at 72°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Products from AGE and LFD were compared. A standard PCR protocol for the detection of infectious CyHV‐2 (Wang, Xu & Lu ) was also performed using specific primer pair CyHV‐2F (CCTCCGTATCTTTGGGGACT) and CyHV‐2R (ATGATGCCCTCAAAGGTGTC); Table . PCR amplification conditions were as follows: initial denaturation at 98°C for 1 min, followed by 35 cycles of 10 s at 98°C, 10 s at 55°C and 60 s at 72°C, and a final extension at 72°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Crucian carp was obtained from the Shanghai Ocean University fish breeding farm. According to the previous method (Xu, Podok, Xie, & Lu, 2014), the CyHV-2 virus (Wang, Xu, & Lu, 2016) was isolated from diseased crucian carp kidney, spleen and liver using sucrose gradient centrifugation and stored at À80°C.…”
Section: Fish and Pathogensmentioning
confidence: 99%
“…The virus seems to be widely distributed in the world, and it was detected in Japan (Jung & Miyazaki, ), USA (Goodwin, Sadler, Merry, & Marecaux, ), China (Luo et al., ), Australia (Stephens, Raidal, & Jones, ) and recently in several European countries including the UK (Jeffery et al., ), France (Boitard et al., ), Switzerland (Giovannini et al., ) and Italy (Fichi et al., ). More critical for attempts to limit the spreading of the disease is the observation that surviving individuals become chronic carriers of a most probably latent infection without displaying external clinical signs (Wang, Xu, & Lu, ).…”
Section: Pcr Conditions Including Primer Sequences Annealing Temperamentioning
confidence: 99%
“…Both PCRs were performed as described earlier (Jung-Schroers et al, 2016). These were followed by two PCR protocols for the detection of CyHV-2, an endpoint PCR targeting a fragment of the viral DNA helicase (Waltzek, Kurobe, Goodwin, & Hedrick, 2009) and a SYBR Green quantitative PCR (Wang et al, 2016). All primer sequences, annealing temperatures and number of cycles are indicated in Table 1.…”
mentioning
confidence: 99%
“…One report found that formalin‐inactivated vaccine that was inoculated by intraperitoneal injection and immersion were both effective to against CyHV‐2 infection in goldfish, this operable vaccination method provides us with an effective prevention method ( Ito & Ototake, ). Otherwise, CyHV‐2 replicated in peripheral blood cells as well as in liver, kidney and gill, thus haematological examination might provide a nonlethal viral detection method to detect rare and expensive fish species infection (Wang, Xu, & Lu, ). Metabolic study of CyHV‐2 infected Crucian carp has shown several biochemical changes, while more specific study of CyHV‐2 infection mechanism should be conducted (Tang et al, ).…”
Section: Discussionmentioning
confidence: 99%